Preference and attitude of project manager toward timber as building and construction materials - Hisamuddin, Siti Hajar (2018)
There is currently a limited use of timber product in residential development in Malaysia due to the dominance of heavy material such as concrete, steel and brick. This dominant use of heavy material is a reversal of the traditional material choices that was based predominantly on timber products. There are many weakness of timber compared with other material that makes construction sectors in Malaysia are not interested in using timber such as inconsistent and lack quality, high costs and fluctuated on the availability of the material. Even timber consumption stated may be more environmental friendly, perception of project managers are not only focused on the completed appearance of the building. This study was carried out to determine the attitude of the project managers toward timbers as construction and building materials and to analyses the preference of the project managers toward timbers as construction and building materials. The total 38 project managers from different companies have participated in answering the questionnaire related to their preference and attitude. In section 4.4 stated that most of the project managers have a positive attitude toward timber but still they concerned about price and maintenance of the material. About the preference project managers, even they have positive attitude towards timber as building and construction material, project managers in this study are not preferred to invest timber to be part of their building construction. It due to the prices of timber is higher than non-timber construction materials, they have lack in technical knowledge to deal with timber and amount of skilled worker to work with timber are limited.